Gaussian mixture multitarget–multisensor Bernoulli tracker for multistatic sonobuoy fields. Issue 12 (1st December 2017) - Ristic, Branko; Angley, Daniel; Suvorova, Sofia; Moran, Bill; Fletcher, Fiona; Gaetjens, Han; Simakov, Sergey
Abstract : Sonobuoy fields, consisting of a large network of emitter and receiver sonar sensors on buoys, are increasingly being used for detection and tracking of underwater targets in a defined maritime area. This study presents a Gaussian mixture version of a multitarget–multisensor (MS) Bayesian‐type tracker developed specifically for multistatic sonobuoy fields. Its foundation is the optimal Bayesian MS filter for a single target in clutter. The multi target feature is incorporated using the linear‐multitarget paradigm, which is a fast and accurate approximation assuming the density of underwater targets is low. Reliable track initiation and false track discrimination for low signal‐to‐noise ratio targets are achieved using the amplitude feature of reported detections. The developed tracker is capable of processing measurements with different modalities, depending on the transmitted signal waveform. It is integrated and tested within a realistic multistatic sonar emulator developed by DST Group.